ANALISIS SENGKETA PAJAK ATAS PEMBATASAN PERBANDINGAN UTANG DAN MODAL PERUSAHAAN - Ajeng Loshita Sari; Siti Nuryanah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
This study aims to analyze the causes of thin capitalization disputes after the implementation of related rules (PMK Number 169/PMK.010/2015 (PMK-169)) based on the Tax Court's decision from 2019 to 2022. The research method is qualitative using a triangulation approach by conducting content analysis and documents, interviews and data triangulation using more than one data source over several time periods. The results of the research show that there has been an increase in the number and causes of disputes related to thin capitalization after the implementation of regulations. This is due to the use of a fixed ratio of debt and equity of 4:1 which is seen as not in accordance with the characteristics of the business and does not reflect fairness in business. The cause of the dispute also comes from the weakness of the examiner's correction basis in proving fairness and the existence of tax evasion efforts. This research has implications for efforts to minimize the occurrence of tax disputes in the future, accelerate tax dispute resolution and increase literacy, especially related to thin capitalization in Indonesia.